Peran Pemerintah Desa dalam Menurunkan Tingkat Kemiskinan di Desa Sukajaya Kecamatan Pamarican Kabupaten Ciamis - Ismi Islaminati; Neti Sunarti; Asep Nurdin Rosihan Anwar (Pusat Riset dan Inovasi Nasional, 2025)
The problem of poverty is a serious problem found in areas especially rural Poverty is one of the main indicators in evaluating the progress of a village. Therefore, each village tries to carry out a number of activities to reduce poverty. Especially in Sukajaya Village, Pamarican District continues to try to reduce the poverty rate in Suakajaya Village through development and assistance using village funds. This study used the theory of Prof. Dr. Sondang P. Siagian, M.P.A. which aims to examine and analyze how the village government plays a role in lowering poverty levels using five role dimensions: Role as Stabilizer, Role as Innovator, Role as Modernizer, Role as Pioneer, and Role as Self-executor. This study used qualitative descriptive research with interviews and literature as its data collection. This study results in the fact that the government of Des Sukajaya has tried to make efforts to reduce the poverty rate in Desa Sukajaya, but the efforts made by Desa Sukajaya have not been carried out properly because there are still programs carried out by Desa Suakjaya that have not been optimally and there are still programs which will begin to know the front. However, the Sukajya village government continues to strive to maximize the programs in the village in the welfare of the community by mobilizing the younger generation to conduct training.